Les organisations publiques d’aide au développement et la dialectique environnement-développement - Tiphaine Lemenager; Aurélie Ahmin-Richard; Laurent Mermet (VertigO, 2012)
Recognizing that there are both synergistic as well as paradoxical dimensions within the Environment - Development dialectic, this paper examines the question of how an aid agency may favor a development taking environmental challenges into account. Strategic reading of current debates in this respect leads us first to propose a typology that identifies the extent to which proponents of a position give greater or lesser priority to the environment with respect to development. Based on this grid, we focus more specifically on donors through an analysis of the French Development Agency. We therefore propose to compare the environmental ambitions of this actor with the various efforts it makes. Is it enough, or is it too little? The answer obviously depends on the general perspective that is adopted on environmental issues. But for those who wish to integrate the environment (an integration which must be pursued), and for those who want to stress the importance of this issue (a move which must be taken), it clearly appears that aid agencies have to continue the great efforts already being made. To conclude, our study identifies a few questions and research opportunities that seem relevant to develop in order to advance in this direction.